Chemical ecology in aquatic systems - Brönmark, Christer; Hansson, Lars-Anders (Oxford University Press, 2012)
In recent years it has become increasingly clear that chemical interactions play a fundamental role in aquatic habitats and have far-reaching evolutionary and ecological consequences. A plethora of studies have shown that aquatic organisms from most taxa and functional groups respond to minute concentrations of chemical substances released by other organisms. However, our knowledge of this ""chemical network"" is still negligible. Chemical interactions can be divided into two largersub-areas based on the function of the chemical substance. First, there are interactions where chemical substance